2018
DOI: 10.2217/nnm-2017-0342
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Fibronectin Fragment III8-10/polylactic Acid Hybrid Nanofibers Enhance the Bioactivity of Titanium Surface

Abstract: Coating of Ti implants with hybrid CAS/PLA NFs may improve significantly their osseointegration potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 57 publications
2
5
0
Order By: Relevance
“…Noteworthy, the mineralization at 21 days was also higher when the Ti scaffolds were functionalized with CAS compared to the nonfunctionalized scaffolds (Figure 8c). These results are in agreement with previous studies, notwithstanding that it was found that the CAS fragments did not stimulate cell differentiation nor mineralization per se [35,60], when the CAS fragments were present in a three-dimensional matrix synergistic effects on cell differentiation were found between the CAS fragments, the increased roughness and the three-dimensional architecture [46]. Similarly, in this case, we hypothesize that the three-dimensional architecture of the scaffolds along with the filament roughness and the presence of CAS synergistically enhanced the differentiation and mineralization of SaOS-2 cells [54,61].…”
Section: In Vitro Cell Responsesupporting
confidence: 93%
See 3 more Smart Citations
“…Noteworthy, the mineralization at 21 days was also higher when the Ti scaffolds were functionalized with CAS compared to the nonfunctionalized scaffolds (Figure 8c). These results are in agreement with previous studies, notwithstanding that it was found that the CAS fragments did not stimulate cell differentiation nor mineralization per se [35,60], when the CAS fragments were present in a three-dimensional matrix synergistic effects on cell differentiation were found between the CAS fragments, the increased roughness and the three-dimensional architecture [46]. Similarly, in this case, we hypothesize that the three-dimensional architecture of the scaffolds along with the filament roughness and the presence of CAS synergistically enhanced the differentiation and mineralization of SaOS-2 cells [54,61].…”
Section: In Vitro Cell Responsesupporting
confidence: 93%
“…The CAS fragment has been described to promote cell proliferation in smooth Ti surfaces [31]. Moreover, Guillem-Marti et al have studied the adhesion and proliferation of SaOS-2 cells on smooth Ti, obtaining similar results on adhesion and proliferation than the Ti scaffolds used as a control in this work, which demonstrates the biocompatibility of uncoated Ti [46,57]. In this study, however, the Ti surface presents pores that have been shown to affect protein adsorption processes through capillary forces and increased specific surface area [58].…”
Section: In Vitro Cell Responsesupporting
confidence: 64%
See 2 more Smart Citations
“…Due to its diverse properties in regulating both osteogenic and supporting cell types, along with orchestrating the assembly of various other ECM proteins and GFs, incorporating FN into regenerative medicine applications is under intensive research (Xing et al, 2017;Cheng et al, 2018;Escoda-Francolí et al, 2018;Guillem-Marti et al, 2018;Parisi et al, 2019a;Sánchez-Garcés et al, 2020;Toffoli et al, 2020;Trujillo et al, 2020;Zhang et al, 2020). Lee et al (2019) recently developed an FN fusion protein, containing FNIII 9-10 domain and elastin like peptides (FN-ELP) to more reliably recapitulate mechanical properties of native ECM.…”
Section: Recent Advancements In Fibronectin-based Biomaterialsmentioning
confidence: 99%